(3JMQjQ cJGH GdCaYGds - (3Ydj Hf LYaQ Hf Ydj GdSYOj, CHh GdbGSe, GdSYOj GdUbdj GdeUQj, GdeYQha H GHf GdbWGY,J (B515 (3g` s; (3eMeO Hf YeQ Hf YHO GdYRjR Hf EHQGgje GdCfOdSj, CHhHcQ GHf GdbhWjg,J (B367 (3g` s
(3ChdgG (B:s
(3bGd GHf GdbWGY EYde Gf GaVd eG QZH ajg GdQGZH hJYdb Hg GdWGdH eYQha dZI GdYQH GdJi fRd HgG GdbQBf hhQO HgG MOjK GdfHi Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3jfJgi HHGH GdKfGFi GdecQQ s
(3GdejcQhajde Hg Jda HSjWs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs